EFFECTIVE SCHEMES OF THERAPEUTIC AND PREVENTIVE MEASURES FOR DISEASES OF THE ORAL CAVITY IN PROFESSIONAL ATHLETES - Gadjiyev, J.G. (World of Medicine and Biology, 2020)
550 professional athletes aged 17-33 years with high sports qualifications were examined. When organizing treatment groups in the form of control, a group of 20 athletes who did not pass the course of treatment and prevention measures, of the same age, sports qualifications and somatic status as in the main group was selected (20). In the control group, the prevalence of apical periodontitis was 3.0±1.71%, in the groups with CVS diseases – 13.3±2.78% (p
Keywords: athletes; caries; pulpitis; periodontitis; treatment